Posted by **math** on Monday, November 1, 2010 at 3:16pm.

Right answer?

15(x^2+3x) + 7(x^2+3x) - 5(x^2+3x)

15x^2+45x+7x^2+21x + 5(-x^2-3x)

15x^2+45x+7x^2+21x-5x^2-15x

17x^2+51x

- lomas -
**Henry**, Wednesday, November 3, 2010 at 4:46pm
x^2 + 3x is common to all terms. So we

factor it out:

(x^2 + 3x) (15 + 7 - 5),

(x^2 + 3x)17,

17(x^2 + 3x).

Factor your answer and it wil be identical to mine.

Alternate method:

Let (x^2 + 3x) = a,

15a + 7a - 5a = 17a,

17(x^2 + 3x).

## Answer This Question

## Related Questions

- algebra - -15(3+x)=-6x-9 -45-15x=-6x-9 -45-15x+15x=-6x+-15x-9 -45=21x-9 -45=x-9...
- Algebra - I need help trying to put the correct vocabulary words when solving ...
- Math - Simplify I came up with 5.5 (15x^5-21x^4+21x^2)/(3x^2 ) not sure if I did...
- Math(Please check my work.) - (2x-3)(x^2+5x-3)=2x+10x^2-15x+9 *Is this correct...
- Algebra - I need help trying to put the correct vocabulary words when solving ...
- math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...
- Math (logarithmic functions) - Those are the only ones I can't seem to resolve. ...
- math,correction - Directions:Multiply Problem: ((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(...
- Intermediate Algebra - Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^...
- algebra - Andrew factored the expression 54x^3-30x^2+15x as 5x(9x^2-6x+3) but ...

More Related Questions